The Effect of Adding Maltodextrin and Sucrose on The Physicochemical Characteristics of Jackfruit Seed Milk Powder (Artocarpus heterophyllus, Lamk) - Suparno; Wijantri Kusumadati; Evi Faridawaty; Ivan Lassan; Devi Fatmawati; Arief Rahman (Politeknik Pertanian Negeri Samarinda, 2025)
Jackfruit seeds are a food source that contains carbohydrates, protein, fat, and minerals such as phosphorus, iron, and calcium. Jackfruit seeds can be used to make powdered milk. Milk has many functions and benefits, including preventing osteoporosis and keeping bones strong. Milk is essential for children's bone development. The purpose of this study was to determine the effect of adding maltodextrin and sucrose on the physicochemical and organoleptic properties of milk powder made from jackfruit seeds. This study used a completely randomized factorial design, with the first factor being the addition of maltodextrin at 3, 5, and 7% and the second factor being the treatment of sucrose at 2, 4, and 6%. Each treatment was repeated three times. The results indicated that the interaction between maltodextrin and sucrose treatments had a significant effect on moisture content, protein, fat, and phenolic content but did not significantly affect the organoleptic tests for color and taste. The single factor of sucrose addition had a significant effect on the organoleptic tests for color and taste. The best treatment for making jackfruit seed milk powder was at 5% (maltodextrin) and 4% (sucrose), resulting in moisture content (8.95%), protein (4.98%), fat (4.34%), and phenolic content (105.80 mgGAE/g). Meanwhile, jackfruit seed powder milk with the most preferred organoleptic characteristics was produced with the addition of 6% (sucrose), resulting in organoleptic characteristics of color 5.02 (somewhat liked) and taste 6.02 (liked).